Interpersonal communication style of pre-marriage couples in toxic relationships (BIS Humanities and Social Science, 2025)
This study describes the interpersonal communication styles exhibited by couples in toxic pre-marriage relationships and the impact of these communication styles. The method used in this research is descriptive qualitative. Data were collected through in-depth interviews. The data validity test technique uses data triangulation. The data analysis techniques in this study include data collection, data reduction, data presentation, and verification. The research results show couples A and B’s communication style is dynamic style because they tend to be aggressive, rebellious, curse, throw things, and hit their partner during communication. C and D use the controlling style of communication, characterized by controlling social interactions, forcing compliance with their desires, limiting interactions, and threatening with consequences and demands. E and F have the withdrawal style of communication, characterized by silent treatment and avoiding communication, resulting in a lack of two-way communication and insufficient interaction between both parties. The impact caused by toxic communication styles includes physical injuries, discomfort, pressure, depression, stress, anxiety, and even self-harm. Advice for couples in a toxic pre-marital relationship is to end the relationship if it is toxic to avoid toxic behavior and its consequences.